Tpks Law as an Effort to Prevent Relations of Power in Sexual Violence in Religious Education Institutions - Toni Kurniawan; Anna Zakiah Derajat (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Cases of sexual violence in Islamic boarding schools are currently a public concern. The existence of vulnerability to women as victims of criminal acts of sexual violence is caused by several factors, such as the occurrence of power relations in the pesantren environment. Therefore, this paper aims to explore the construction of sexuality, social, knowledge, and power relations that have an important influence on the persistence of patriarchal discourse in society, especially in religious education institutions or Islamic boarding schools. In analyzing the problems in this study, the author uses Michel Foucault's theory of power relations with the literature study data search method. The results show that asymmetric power relations are formed and abused to carry out various acts of sexual violence that are controlled under various pretexts of the principle of obedience that must be carried out by a santri against his kiai, gus, or ustaz. In addition, various forms of religious norms, stereotypes, and stigmatization that exist also perpetuate the power of knowledge that is used as a tool for sexual harassment in Islamic boarding schools. For this reason, various efforts are needed to prevent acts of sexual violence, such as the existence of sexual education in the pesantren curriculum, the post for complaints of sexual violence, and the role of national and regional governments to oversee the case. In this case, the ratification of the TPKS Law can also provide fresh air to ensnare perpetrators of sexual violence in Islamic boarding schools.